KAJIAN GERAKAN FEMINISME PADA KARYA-KARYA NAWAL EL-SAADAWI - Sari, Raras Hafiidha (STKIP PGRI Jombang, 2022)
Author Nawal el-Saadawi is a feminist from Cairo, Egypt whose work focuses on women in Islam. After El-Saadawi obtained his medical degree at Cairo University in 1955. El-Saadawi through his medical practice, he observed physical and psychological problems in women and related them to real-life stresses, patriarchal cultural domination, class pressures, and imperialism. El-Saadawi is known as a feminist so she writes extensively on women's issues through her medical practice. As a doctor, he tries to describe the physical and psychological problems of women and then relate them to culture, gender, and patriarchy. According to the results of his research, El-Saadawi uses it as a literary work in the form of novels and short stories. In her literary work, there are several perspectives on women's issues that cannot be separated from her feminism. Through her works, she tries to fight for women's issues. In this article, the author will question and review how the form of Nawal el-Saadawi's feminist movement is contained in her writings, both as novels and as short stories. Meanwhile, the purpose of writing this article is to reveal and describe the feminist thought of Nawal el-Saadawi and the feminist movement that she includes in her works. The data sources used are el-Saadawi's writings, both fiction and non-fiction. In addition, other sources related to el-Saadawi and feminism in the Middle East, especially Egypt, are also used both in book form and on the internet.